2016
DOI: 10.7554/elife.10762
|View full text |Cite
|
Sign up to set email alerts
|

Massive cortical reorganization in sighted Braille readers

Abstract: The brain is capable of large-scale reorganization in blindness or after massive injury. Such reorganization crosses the division into separate sensory cortices (visual, somatosensory...). As its result, the visual cortex of the blind becomes active during tactile Braille reading. Although the possibility of such reorganization in the normal, adult brain has been raised, definitive evidence has been lacking. Here, we demonstrate such extensive reorganization in normal, sighted adults who learned Braille while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
101
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 80 publications
5
101
3
2
Order By: Relevance
“…The visual cortex becomes recruited for tactile and auditory perception in the blind (1,2,6,8,13,16,17,(41)(42)(43), and the auditory cortex becomes recruited for tactile and visual perception in the deaf (20-23, 26-29, 44). Such large-scale reorganization is also possible after intensive training in nondeprived subjects (5,12,(45)(46)(47)(48)(49). In particular, the ventral visual cortex was shown to be critical for learning tactile braille reading in sighted adults (5), suggesting that such plasticity could be the mechanism underlying complex learning without sensory deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The visual cortex becomes recruited for tactile and auditory perception in the blind (1,2,6,8,13,16,17,(41)(42)(43), and the auditory cortex becomes recruited for tactile and visual perception in the deaf (20-23, 26-29, 44). Such large-scale reorganization is also possible after intensive training in nondeprived subjects (5,12,(45)(46)(47)(48)(49). In particular, the ventral visual cortex was shown to be critical for learning tactile braille reading in sighted adults (5), suggesting that such plasticity could be the mechanism underlying complex learning without sensory deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Such large-scale reorganization is also possible after intensive training in nondeprived subjects (5,12,(45)(46)(47)(48)(49). In particular, the ventral visual cortex was shown to be critical for learning tactile braille reading in sighted adults (5), suggesting that such plasticity could be the mechanism underlying complex learning without sensory deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the occipital cortex, as well as adjacent ventral areas such as the fusiform gyrus (16,17), have been the main regions of interest in the study of cross-modal phenomena in blindness. Multiple studies have shown that the occipital cortex takes over multiple sensory abilities traditionally belonging to other unimodal cortices, such as auditory (18,19), tactile (20), or higher cognitive functions, including language processing (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it seems natural to ask whether the mechanism of task-specific brain reorganization is limited to the very particular circumstances of prolonged sensory deprivation. Previous studies on visual cortex have already shown that some forms of task-specific recruitment of the visual cortex are possible in nondeprived adults, either after several days of blindfolding (16) or after extensive tactile or auditory training (6,17,18). In their experiment, Benetti et al (2) report a marginally significant trend in the fMRI adaptation effect for faces in hearing participants, suggesting that the temporal voice area may have a similar cross-modal potential for face discrimination in both hearing and deaf subjects.…”
mentioning
confidence: 99%